Farmers Experiencing Potato Seed Degeneration Respond but Do Not Adjust Their Seed Replacement Strategies in Ecuador - Navarrete, I.; Andrade-Piedra, J.L.; López, V.; Yue, X.; Herrera, J.; Barzallo, M.; Quimbiulco, K.; Almekinders, Conny J.M.; Struik, P.C. (Springer, 2023)
In Ecuador, farmers poorly adopt practices to manage potato seed degeneration. This could be related to the deficient understanding of the farmers' capacity to experience seed degeneration and respond to it. We contribute to this understanding by answering: How do farmers experience seed degeneration?; What practices do farmers implement when their seed is degenerated?; and Is experiencing degeneration the pivotal factor determining how farmers replace their seed regardless their income? We analysed data collected in Ecuador through farmers' focus group discussions, farmers' surveys and interviews, and the Ecuadorian employment status survey. We found that approximately half of the farmers experienced degeneration. Farmers experienced it through low yields, change in seed appearance, crop weakening, and seed physiological problems. When farmers experienced degeneration, they replaced their seed, sought for technical advice, applied more agricultural inputs, or grew other crops. Income was an important trigger for farmers to change their seed replacement practices.